Exploring students mathematical communication in guided inquiry and STAD cooperative learning models - Lishani, Jenita Eka; Yuniarti, Tina; Gunowibowo, Pentatito (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to investigate the effect of guided inquiry and Student Teams Achievement Division (STAD)-type cooperative learning models on students’ mathematical communication ability. A quasi-experimental method with a pretest-posttest control group design was employed. The sample consisted of two eighth-grade classes selected through cluster random sampling from a junior high school in Bandar Lampung. Students in the experimental class received instruction using the guided inquiry model, while those in the control class were taught using the STAD-type cooperative model. A mathematical communication test, consisting of items aligned with three key indicators—written explanations, symbolic expressions, and visual representations—was administered before and after the intervention. Data were analyzed using an Independent Samples t-test. The results revealed a statistically significant difference in posttest scores between the two groups (t = 2.844, p < 0.05), favoring the guided inquiry model. Additionally, students taught through guided inquiry demonstrated greater improvements across all indicators of mathematical communication, particularly in their ability to explain reasoning through structured written responses and to use appropriate mathematical symbols.